Automotive heating and air conditioning - Halderman, James D. (Boston Pearson, 2018)
Book is provides a complete, state-of-the-art source on automotive heating, ventilation, and air conditioning systems, as well as the practical skills that students must master to be successful in the industry
Includes bibliographies and index.
Keywords: Công nghệ kỹ thuật ô tô